The Three-Dimensional Perspective of Artificial Intelligence-Aided University English Course Reform from the Perspectiveof Core Disciplinary Literacy - Zhang, Jiarui (Journal of Educational Theory and Practice, 2025)
Artificial intelligence, as an emerging educational technology, has gradually penetrated into the reform of university English curriculum and become an important tool for promoting educational innovation and improving teaching quality. This paper is based on the significance of artificial intelligence to help the reform of university English curriculum, for the current reform of university English curriculum is faced with the teaching concept to be updated, teaching content and methods to be perfected and the construction of teachers to be strengthened and so on, puts forward the promotion of the innovation of teaching concepts, improve the content and methods of teaching and strengthen the construction of teachers, etc., which provides some references to the promotion of China’s university English education reform.